Triazonine-based bistable photoswitches: synthesis, characterization and photochromic properties. Issue 78 (13th September 2021) - Goual, Nawel; Casimiro, Lorenzo; Delattre, Vincent; Retailleau, Pascal; Maisonneuve, Stéphane; Bogliotti, Nicolas; Métivier, Rémi; Xie, Juan; Marinetti, Angela; Voituriez, Arnaud
Abstract : Dibenzotriazonines, a new class of nine-membered cyclic azobenzenes, have been developed and have demonstrated good thermal stability for both E - and Z -isomers. Abstract : We disclose here dibenzotriazonines as a new class of nine-membered cyclic azobenzenes displaying a nitrogen function in the saturated ring chain. The specific features of these compounds are (i) a preferred E -configuration, (ii) high bi-directional photoswitching and (iii) good thermal stability of both E - and Z -forms.